Transoral Robotic Surgery - An Inevitable Future of Oral and Maxillofacial Surgery - Dr. Seema Shantilal Pendharkar (Rajiv Gandhi University of Health Sciences, 2024)
With the advancements in oral surgical procedures minimally invasive surgery has gained prime importance to avoid the drawbacks associated with conventional surgical procedures in the head and neck region. In 2005 robotic surgery was used in the management of head and neck tumors and various non neoplastic diseases. Transoral robotic surgery TORS demonstrated several advantages such as being minimally invasive reduced intraoperative blood loss decreased post operative hospital stay preservation of adjacent structures accurate dissection and decreased post operative tissue morbidity with improved patient compliance. The application of TORS is still in the experimental stage and requires more research to establish its wide spread use. Although its development is inevitable and proves to be a boon for the expanding future of oral and maxillofacial surgery the results seem to be promising. This review highlights the current application of roboticTORS procedure its benefits and limitations in the head and neck region.